STUDI KASUS KLAIM MALAYSIA ATAS BERAS ADAN KRAYAN PROVINSI KALIMANTAN UTARA - Sugiharto, Didit (TANJUNGPURA LAW JOURNAL, 2024)
AbstractAs a country that has biodiversity spread across various regions in Indonesia, it is not impossible for the local varieties owned by regions in Indonesia is not impossible for local varieties owned by other countries. Indonesia is recognized by other countries, with the geographical fact that there are many areas that border directly with other countries. That border directly with other countries. Cases of claims on local varieties owned by Indonesia as done by Malaysia which claims local plant varieties owned by Indonesia, namely adan rice which is located in the highlands of highlands of Borneo, Krayan District, Nunukan Regency, North Kalimantan, which is a potential border area between Indonesia and Malaysia. The incident of the claim must become an awareness of the importance of legal protection of local varieties owned by Indonesia that have high economic potential Indonesia that have high economic potential.  AbstrakIndonesia sebagai negara yang memiliki keanegaragaman hayati yang tersebar di berbagai daerah di Indonesia bukan tak mungkin terhadap varietas lokal yang dimiliki Indonesia di kliam oleh Negara lain, dengan fakta geografis terdapat banyak daerah"“daerah yang berbatasan langsung dengan negara lain. Kasus klaim atas varietas lokal milik Indonesia seperti yang dilakukan oleh Malaysia dimana mengklaim varietas tanaman lokal milik Indonesia yaitu beras adan yang berada di dataran tinggi Borneo, Kecamatan Krayan, Kabupaten Nunukan, Kalimantan Utara, yang menjadi potensi daerah perbatasan RI-Malaysia. Peristiwa klaim tersebut harus menjadi sebuah kesadaran akan pentingnya perlindungan hukum atas varietas lokal yang dimiliki oleh Indonesia yang memiliki potensi ekonomis yang tinggi.